Perbandingan Metode SAW dan TOPSIS untuk Pemeringkatan IPM di Jawa Tengah Tahun 2024 - Kristiyono, Budi; Alfiqhyanto, Damas; Ariyanto, Eko; Nugroho, Kristiawan; Ardhianto, Eka (STIKOM Tunas Bangsa Pematangsiantar, 2025)
The Human Development Index (HDI) is an important indicator for assessing the success of regional development, particularly in the aspects of health, education, and economy. However, as an aggregate indicator, HDI cannot yet specifically represent the unique development needs of each region. Therefore, a decision support system (DSS) approach is needed to analyze HDI components more deeply and objectively. This study aims to compare two multicriteria decision-making methods-Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS)-in ranking the HDI of regencies/cities in Central Java Province in 2024. The HDI data was obtained from the Central Statistics Agency (BPS) 2024, covering the three main dimensions of HDI. The analysis results show differences in ranking orders between the two methods, indicating that the choice of analytical method can influence development interpretations and priorities. This study makes a significant contribution by providing a data-driven approach to support more targeted regional development policies.